Duration calculus semantics for statecharts - Sánchez, Marisa (2002)
Statecharts and Duration Calculus are two formalisms used in the development of reactive systems. Statecharts provide a powerful visual formalism to specify systems. Duration Calculus is a formal logic to specify and reason about temporal requeriments. In this work, we propose a description of statecharts semantics using Duration Calculus. Thus we build a common semantic model for Duration Calculus speci¯cations and statecharts. The formalization is done in two steps. First, the structure of a statechart is represented using Duration Calculus formula. Then, the semantics of the execution of a step is introduced.